To solve the quadratic equation \( x^2 - 6x - 16 = 0 \) using the quadratic formula, we use the formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
where \( a = 1 \), \( b = -6 \), and \( c = -16 \).
-
Calculate \( b^2 - 4ac \):
\[ b^2 - 4ac = (-6)^2 - 4 \cdot 1 \cdot (-16) \] \[ = 36 + 64 = 100 \]
-
Substitute values into the formula:
\[ x = \frac{-(-6) \pm \sqrt{100}}{2 \cdot 1} \] \[ = \frac{6 \pm 10}{2} \]
-
Calculate the two possible solutions:
For the positive root:
\[ x = \frac{6 + 10}{2} = \frac{16}{2} = 8 \]
For the negative root:
\[ x = \frac{6 - 10}{2} = \frac{-4}{2} = -2 \]
So the solutions to the equation \( x^2 - 6x - 16 = 0 \) are \( x = 8 \) and \( x = -2 \).
The correct response is:
x=8, x=−2
x equals 8 , x equals negative 2